Asset Growth In Sharia Insurance: Macroeconomic and Internal Factors of Sharia Insurance Companies in Indonesia - Hilmy Baroroh (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2021)
AbstractSharia insurance presents an alternative system in insurance operation with risk sharing in ta'awun (cooperative). Knowledge and insight into reality and trends are used to assess and decide sharia insurance operationalization policies. This study analyzed the growth of Islamic insurance company assets in Indonesia in 2016-2020. The data is sourced from the Sharia Financial Statement Statistics published by OJK and Bank Indonesia Statistics from 2016 - 2020 with multiple linear regression analysis methods. This research aims to find out the influence of internal variables and external variables on the assets growth of sharia insurance in Indonesia. In this study, there are two variables, namely dependent variables and independent variables. Dependent variables are the assets growth of sharia insurance in Indonesia (PERASSET), and independent variables, namely GDP (GDP), inflation (INF), contribution (KONB), investment (INVEST), and operating costs (BOPERATE). The results of this study GDP, Inflation, Contributes, and Investment affects Sharia insurance's assets growth. While operating costs do not affect the assets growth of sharia insurance companies.Keywords: Sharia Insurance, Asset Growth, GDP, Inflation, Contribution, Investment, Operating Costs